SPEECH ACTS IN PSYCHOLINGUISTICS CLASS SETTING IN POSTGRADUATE PROGRAM - Lalu Suhirman (Center of Language and Cultural Studies [CLCS], 2016)
This article aims to identify forms of speech act in the lecture of psychololinguistics class setting and to elaborate types of speech act approaches in the lecture. The subjects of this research are an English instructor and 11 psycholinguistic participants of Post Graduate Program of UNM. Data taken from this study were the utterances produced by instructor/lecturer and the participants during the class discussion. Instruments of this study were observation format, field notes, tape recorder/and handy-camp, and the script of utterances. The result of analysis indicated that there were three types of speech acts: locutionary actillocutionary act, and perlocutionary act. The speech acts has an effect on the feelings, thoughts or actions of either the speaker or the listener. The speech acts change readers or listeners mindset.